2018
DOI: 10.1093/geront/gny025
|View full text |Cite
|
Sign up to set email alerts
|

What Consumers Say About Nursing Homes in Online Reviews

Abstract: Our results are consistent with those from related studies. Yelp reviewers focus on NH aspects that are not evaluated in most other NH rating systems. The federal Nursing Home Compare website, for instance, does not report measures of staff attitudes or the NH's physical setting. Rather, it reports measures of staffing levels and clinical processes and outcomes. We recommend that NH consumers consult both types of rating systems because they provide complementary information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 7 publications
1
12
0
1
Order By: Relevance
“…Consistent with prior studies, [34][35][36] Our findings also highlight previously noted concerns with online information about health care facilities. We were unable to obtain demographic information about the review website reviewers or the nature of their experience with the facilities (eg, timing and duration of stay, relationship to the patient).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with prior studies, [34][35][36] Our findings also highlight previously noted concerns with online information about health care facilities. We were unable to obtain demographic information about the review website reviewers or the nature of their experience with the facilities (eg, timing and duration of stay, relationship to the patient).…”
Section: Discussionsupporting
confidence: 91%
“…The themes associated with positive and negative experiences can supplement information from other sources to create a more holistic view of factors that are important to patients and their families. Several other studies of online review data have identified similar factors as associated with positive (good staff behaviors, compassion) and negative experiences (wait time, poor communication, poor accommodations) [4][5][6][7][8][9] ; the endurance of these findings across settings highlights systemic issues around the design and provision of healthcare services. The discrepancy between themes identified in online reviews and information in the NSSATS is not surprising, however, since NSSATS and review sites have different objectives.…”
mentioning
confidence: 82%
“…Insights from these data may be able to shed additional light on what is important to the patient experience. Studies of themes emerging from online reviews of hospital, [4][5][6] emergency department, 7 urgent care, 7 pharmacy, 8 and nursing home 9 settings have been conducted, but not much is known about the content of online reviews for substance use treatment facilities.…”
mentioning
confidence: 99%
“…Research in hospitals and nursing homes has found that Yelp reviewers tend to focus on subjective experiences of health care, such as their personal assessments of staff attitudes, rather than clinical aspects of care (e.g., pain management). 11,12 Consumer review sites such as Yelp are widely known for both their strengths and weaknesses. Some online consumer reviews, for instance, are faked.…”
Section: Yelpcommentioning
confidence: 99%